POTRET TELEVISI DI INDONESIA (Kajian Perspektif Teori Ekonomi Politik Media dan Kritis) - Herdono, Ismojo (Scriptura, 2015)
Barometer used to measure the success of a television media is to capture a sizeable number of spectators it, is called the rating, by simply sticking with the results of rating the rating has been like a 'God' that determine the sustainability of the television media. Television media vying to create a program that can generate the highest rating television or media tries to make a television program or mimic similar television programs from other television stations, is called the mimetisme. Namely, the passion that suddenly attacked by the media and push it, it seems very urgent, rushed to cover the incident because the other media, particularly the reference, consider it important. Approach or methodology used in this studied is a qualitative descriptive approach, by providing study case, is expected to provide a more comprehensive picture about the broadcasting industry, especially television broadcasting industry-national television in Indonesia. The conclusion is, the portrait of the television industry in Indonesia, tend to prefer the interests of the market. Market logic that led to benefit greatly, apparently ignoring the function or role of the media as an educational medium through which the information is correct, dignified and decent.